Analysis of Education Role in Improving the Life Quality of the Orang Laut in Panglima Raja Village Concong Sub District Indragiri Hilir Regency - Haryono, Haryono; Separen, Separen (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research is entitled Analysis of Education Role in Improving the Life Quality of the Orang Laut in the Panglima Raja Village, Concong Sub District, Indragiri Hilir Regency. Researchers are interested in researching because some of the Orang Laut who have studied, the quality of life is not better than fishermen.This research was conducted with the aim to find out how and whether education can improve the life quality of the Orang Laut. This research method is quantitative descriptive, with formula : P = f / n x 100%. The research population is all the Orang Laut Society that has passed the Education Process and has worked for 30 people, This type of research is population research, so the entire population becomes a sample in the study. Data collected through questionnaires, interviews, and later observations from the results of the study can be concluded that the research hypothesis is accepted or proven, this also answers the formulation of the problem, namely, how education changes the quality of life Orang Laut, the results of education only change thinking patterns and understanding of quality life but for the formulation of the problem Is education changing the quality of life of the Orang Laut, the results do not change the life quality of the Orang Laut this is proven by the percentage of 55%, According to Ridwan (2008: 88) the percentage of 55% is enough to state that education does not play a role. In addition, if examined based on Ridwan opinion, the number of tables stating that education plays only 25%, this number is a weak percentage, so it can be concluded that Education does not play a role in Improving the life Quality of the Orang Laut Society in the Panglima Raja Village, Concong Sub District, Indragiri Hilir Regency.